1907 R.I. Pub. Laws 66 - (:unkn) unknown (My University, 1907)
An Act for the Protection of Deer: It shall be unlawful to pursue or shoot deer in this state except in accordance with the provisions of this act.
Keywords: HUNTING REGULATION